1998
DOI: 10.1007/s002030050639
|View full text |Cite
|
Sign up to set email alerts
|

High genetic and physiological diversity of sulfate-reducing bacteria isolated from an oligotrophic lake sediment

Abstract: The community structure of sulfate-reducing bacteria in littoral and profundal sediments of the oligotrophic Lake Stechlin (Germany) was investigated. A collection of 32 strains was isolated from the highest positive dilutions of most-probable-number series, and their partial 16S rRNA gene sequences and genomic fingerprints based on ERIC (enterobacterial repetitive intergenic consensus)-PCR were analyzed. The strains fell into eight distinct phylogenetic lineages, and the majority (70%) showed a close affiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 38 publications
1
50
0
Order By: Relevance
“…Nine different ERIC-PCR fingerprint patterns were detected among the 11 strains, revealing the highest genetic diversity within one 16S rRNA phylotype known so far. In previous studies, a maximum of three different genotypes with identical 16S rRNA gene sequences were recovered from one environment (27,48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine different ERIC-PCR fingerprint patterns were detected among the 11 strains, revealing the highest genetic diversity within one 16S rRNA phylotype known so far. In previous studies, a maximum of three different genotypes with identical 16S rRNA gene sequences were recovered from one environment (27,48).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some of the 16S rRNA gene sequences (e.g., the two rrsE genes) are identical in the two organisms. Similarly, genomic fingerprinting (48,50,57) and analysis of fosmid libraries of DNA fragments from marine samples (6) have indicated that nonpathogenic bacteria with identical 16S rRNA gene sequences but distinctly different genomes coexist in natural ecosystems (46). The term microdiversity has been used to describe the phenomenon of phylogenetically closely related but physiologically distinct bacterial populations (32).…”
mentioning
confidence: 99%
“…DNA and RNA of each sediment horizon were extracted from 1.5 ml wet sediment by bead-beating, phenol extraction and isopropanol precipitation as described previously (Sahm & Berninger 1998). PCR amplification specific for SRB of the δ-subclass of Proteobacteria was carried out with the forward primer SRB385 carrying a GC-clamp and the reverse primer 907 (Sass et al 1998). DGGE, excision of bands, reamplification, and sequencing were performed as previously described (Muyzer et al 1996).…”
Section: Somentioning
confidence: 99%
“…This might be due to the activity of sulfate reducers at this site, which have so far not been used in experiments on isotope discrimination. In addition, it is known that H 2 S is, to a significant portion, reoxidized, so that sulfur species with intermediate oxidation states may be formed (Jørgensen 1982b), and such that bacterial disproportionation of the latter may lead to the formation of 32 S-enriched H 2 S (Canfield et al 1998, Cypionka et al 1998, Böttcher et al 2001. Indeed, bacteria which are able to disproportionate elemental sulfur, for instance, have been enriched from the sediments at Site Dangast and shown experimentally to discriminate sulfur isotopes (Canfield et al 1998).…”
Section: Biogeochemistry Of the Sedimentmentioning
confidence: 99%
“…However, such "microdiversity" has been reported to make up a significant fraction of the sequence composition of clone libraries (4,10,13,24). That it potentially signifies functional differences is suggested by comparisons between closely related 16S rRNA sequences and physiological properties of isolates (12,32,36) or overall genome architectures (2,18,31,35). In addition, reports of relatively large divergence among rRNA genes between operons have suggested that HGT may affect rRNA genes to a larger extent than was previously assumed (28,40,41,43).…”
mentioning
confidence: 99%